The impact of tax reform to increase the federal budget revenues (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The percentage contribution of tax revenue in the federal budget is verysmall compared with the revenue earned from oil revenues, as the dependenceon oil revenues mainly to finance the state budget, have a negative impact onthe national economy as it makes it a one-sided and prisoner of on revenue, thatis the revenue derived from oil which is unstable revenue for continuouschanging in the price of oil The oil revenues reached to (85.4%) in 2009 withpercentage (93.11%) in 2013, The research objective is to study the possibilityof increasing tax revenues in order to raise the proportion of its contribution infinancing the federal budget through effective tax reforms, The mainconclusion of the research is that the high percentage contribution of oilrevenue in the state budget while the latter (prices of oil) is exposed tofluctuations in prices has been exposed the lraqi economy to significant risks.The recommends Find reform tax system as it is an important element inincreasing budget revenues and its stability through the three variables for thereform, which is building an efficient information base for tax reform andchange tax law to extend to other taxes in addition to the training of qualifiedstaff for tax calculation and application of the effectively tax law.